RELATION BETWEEN LEVEL OF SCHOOLS’ ACADEMIC OPTIMISM AND LEVELS OF ORGANIZATIONAL CYNICISM OF TEACHER’S - BOZ, A.Vahap (Atlas Journal, 2018)
Relation Between level of Schools’ Academic Optimism and levels of Organizational Cynicism of Teacher’s Relationship Between level of Schools’ Academic Optimism and Organizational Cynicism of Teachers’ This study examined the influence of schools" academic optimism on teacher’s organizational cynisim. The study was a relational screening model research. The target population for this study was teachers working in primary and secondary schools located in center of city and districts in Siirt. The first scale was academic optimism scale, developed by Hoy, Tarter, Woolfolk Hoy (2006a) and adopted by Çoban (2010). And the second scale was orgainizational cynisim scale created by Brandes, Dharwadkar and Dean (1998) and adopted by Kalağan (2009). Data was analyzed through SPSS 15 software packet program. Findings from this stdy showed that teachers are moderately encounter cynism mean while teachers. Furthermore, level and perception of teachers’ school academic optimism was meaured as moderate. The most singificant contribution of this study is that academic optimism has negative corelation with organizational cynism. In other words, findings from this study suggests that teachers’ perception of their school’s academic optimism had statistically a negative relationship to teachers’ organizational cynicim. The results revelas that the more schools schools’ level of academic optimism increase, the less teachers feel cynic. Consequently, as to the analyses results, school academic optimism and organizational cynisim were correlated with each other.